Towards an ethics of interpretation: The use of scripture in three recent Christian documents - Oosthuizen, M. J. (Hervormde teologiese studies, 1993)
Three documents have recently appeared which all appeal to Scripture in their elaboration of a vision for the church’s involvement in society. This paper assesses the manner in which the Bible functions within the broader interpretative stance of each document, namely Church and Society, Road to Damascus and Relevant Pentecostal Witness. In order to achieve this, attention is first paid to the establishment of criteria which should form part of a common explanatory commitment to which all position papers should adhere. It is argued that the ideological stance of both the interpreter and Scripture should be acknowledged, so that the relative merits of the various documents can be intersubjectively tested.